Parsec-scale shocks in the kiloparsec-scale jet of Centaurus A - Tingay, Steven; Lenc, E. (Institute of Physics Publishing, Inc, 2009)
High angular resolution very long baseline interferometry (VLBI) observations of Centaurus A have been undertaken that allow access to a wide field of view, encompassing both the well-studied parsec-scale jet and the inner part of the kiloparsec-scale jet. The VLBI observations have detected compact regions of synchrotron emission in the kiloparsec-scale jet that coincide with three stationary features identified from previous VLA monitoring observations. Each of these stationary features is associated with strong localized X-ray emission. The VLBI results strengthen arguments made by previous authors suggesting that the stationary features may be the result of stellar objects or gas clouds traversing the jet flow, intercepting the jet and causing strong shocks. The VLBI data show that the most strongly shocked regions in these features are resolved but have extents no larger than a few pc, reducing the required mass of the typical intercepting object by a factor of -10 relative to previous estimates, making explanations based on high mass-loss stars or low-density gas clouds more plausible.